(3GdCMLGQs - (3CMeO Hf jhSa Hf CMeO Hf CHj HcQ Hf MeOhf GdbjSj GdJjaGTj , TQa GdOjf,J (B651 (3g` s
(3BNQgG (B:s
(3gPG BNQ eG CQOJ EjQGOg hGdTcQ dhGLH GdhLhO CHOkG hUdGJg hSdGeg Ydi CfHjGFg CLeYjf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B273 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B208s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B495 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B904 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WHjYjGJ (B37) s
Keywords: (3GdcjejGA h GdWHjYjGJs